2016
DOI: 10.1016/j.sbspro.2016.05.105
|View full text |Cite
|
Sign up to set email alerts
|

Business Success of Small and Medium Sized Enterprises in Russia and Social Responsibility of Managers

Abstract: This article introduces the authors' approach to the study of business success factors for small and medium sized enterprises. The approach is based on the currently dominant practice of estimating the success of an enterprise as its ability to produce profit. The authors have analyzed the success criteria used by managers of Russian small and medium sized enterprises based on the survey carried out among the managers of 212 small and medium sized enterprises in the period of September -November, 2014, and des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 11 publications
3
34
0
2
Order By: Relevance
“…Therefore, supporting growth and development of SMEs as well as innovative policies targeted at fostering their growth should belong to the state-level priorities (Abrhám et al, 2015;Barkhatov, 2016;Barkhatov et al, 2016;Varanavicius et al, 2017). The state support is provided in financial, property, information and consulting forms and it provides one of the most important prerequisites for regional development (Brodzicki, 2016;Niño-Amézquita et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, supporting growth and development of SMEs as well as innovative policies targeted at fostering their growth should belong to the state-level priorities (Abrhám et al, 2015;Barkhatov, 2016;Barkhatov et al, 2016;Varanavicius et al, 2017). The state support is provided in financial, property, information and consulting forms and it provides one of the most important prerequisites for regional development (Brodzicki, 2016;Niño-Amézquita et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In case of India, Vyas et al (2015) determined CSFs of SMEs in banking in India: Supportive organizational factors, rapid delivery and response to customers, marketing, banking model and policy, and improved customer service. In Russia, Pletnev and Barkhatov (2016) indicated that SMEs are affected by CSFs like employee professional and personal qualities, relations with customers and suppliers, entrepreneurial skills of the top executives, wages, as well as manager's social responsibility.…”
Section: Success Factors Of Smes: a Review Of Literaturementioning
confidence: 99%
“…Scholars from various disciplines agreed on the importance of SMEs success in employment, wealth, and social and economic development (e.g., Autio 2005;Omri and Ayadi-Frikha 2014;Omri et al 2015). According to Pletnev and Barkhatov (2016), SMEs contribute approximately 56% of the gross domestic product (GDP) of many European countries (Muller et al 2017). Similarly, Abdullahi et al (2015) cited additional factors that explain the importance of SMEs, such as communities' empowerment, poverty alleviation and employment opportunities provision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This narrow specialization is based primarily on a limited range of capabilities that are directly related to producing a product or service they understand (Pugna et al, 2016). In such conditions, their main focus is on working practices, but managers often lack strategic and tactical managerial skills (Pletnev and Barkhatov, 2016).…”
Section: Introductionmentioning
confidence: 99%